Exploring the Ethical Dimensions of Halal Supply Chain Management with AI - Abdul Rochim; Fajar Azhari Julian; Ahmad Maulidizen (TechComp Innovations: Journal of Computer Science and Technology, 2024)
This study aims to explore the ethical dimensions of halal supply chain management through the utilization of artificial intelligence (AI). In the context of globalization and the rising demand for halal products, understanding how technology can support not only operational efficiency but also adherence to Islamic principles and ethics is crucial. The research examines the integration of AI technology in each phase of the halal supply chain, from the procurement of raw materials to the distribution of final products. Through literature analysis and case studies, the research identifies the ethical challenges faced at each stage, including transparency, accountability, and fairness in transactions. Furthermore, the study offers recommendations for developing ethical guidelines that can guide effective and responsible halal supply chain management practices. Findings suggest that with the appropriate application of AI, companies can enhance consumer integrity and trust while strengthening their position in the rapidly growing halal market. This research contributes to the existing literature on halal supply chain management and emphasizes the importance of incorporating ethical considerations in the digital era.